2021
DOI: 10.1111/dth.14721
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti‐inflammatory therapies to reduce cardiovascular burden of psoriasis

Abstract: Psoriasis mainly affects the skin and joints and has serious impacts on the physical, emotional, and financial life of patients. Recent studies have demonstrated that other comorbidities are frequently detected in psoriatic patients. A strong association with the development of cardiovascular diseases, such as hypertension, myocardial infarction, and stroke is responsible for the shortened (by 4.5‐5 years) life expectancy of severe psoriatic patients. Systemic inflammation plays an important role in the interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…However, other experimental data and pre-clinical trials do not support a protective effect of biologics against atherosclerotic plaque development (41,42). Some researchers (2,43) summarized the available data about the MACEs risk for the biological products and concluded that TNF inhibitors might reduce the risk of adverse cardiovascular events, the only IL- Paired EBGM values by drug and age groups for MACEs. Note the signal strength (EB05 value by color and the numerical EB05 value being within each minigraph).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other experimental data and pre-clinical trials do not support a protective effect of biologics against atherosclerotic plaque development (41,42). Some researchers (2,43) summarized the available data about the MACEs risk for the biological products and concluded that TNF inhibitors might reduce the risk of adverse cardiovascular events, the only IL- Paired EBGM values by drug and age groups for MACEs. Note the signal strength (EB05 value by color and the numerical EB05 value being within each minigraph).…”
Section: Discussionmentioning
confidence: 99%
“…However, other experimental data and pre-clinical trials do not support a protective effect of biologics against atherosclerotic plaque development ( 41 , 42 ). Some researchers ( 2 , 43 ) summarized the available data about the MACEs risk for the biological products and concluded that TNF inhibitors might reduce the risk of adverse cardiovascular events, the only IL-12/23 inhibitor ustekinumab appeared to be neutral, and the IL-17 inhibitors and IL-23 inhibitors were unclear, although more researches are needed to confirm these findings. A review of current data suggested positive or neutral effect of TNF, IL-17, and IL-12/23 inhibitors on cardiovascular events, but conflicting for IL-23 inhibitors ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous proatherogenic cytokines are elevated in psoriasis, it is worth noting that IL-6, IL-17, IFN-γ and TNF-α assume a prominent role in causing endothelial dysfunction and the development of atherosclerosis. Furthermore, there is an impaired production of vascular NO, which contributes to the occurrence of coronary microvascular dysfunction [60][61][62].…”
Section: The Implication Of Ras In Aidd 71 Psoriasismentioning
confidence: 99%
“…In a recently published review by Piros et al [ 165 ], the authors underline the need for holistic care of patients with severe PSO, which goes beyond skin and joints and by self-reinforcing Th1 and Th17 cell-dependent systemic inflammation, accelerating the progression of metabolic and cardiovascular diseases. Although the intrinsic anti-atherotic potential of novel systemic biologic treatment is still improving, their action should be accompanied, and for older agents, counterbalanced, by further safe and effective preventive measures.…”
Section: Novel Diagnostic and Therapeutic Perspectives In Pso/psamentioning
confidence: 99%